Use of seminal plasma in equine epididymal spermatozoa cryopreservation - Gonzáles Molfino, H. Mauricio (2015)
Equine seminal plasma was used in a lactose-EDTA extender for cryopreservation of equine epididymal sperm. Twelve pairs of testicles of slaughtered horses were used. Epididymides were separated and washed applying the retrograde technique to obtain sperm by injecting 10 ml of lactose-EDTA extender through the vas deferens. Samples with more than 30% motility were used. Samples were diluted 1: 1 with the lactose-EDTAextender seminal plasma and filled into 0.5 ml straws at a concentration of 386.3 x 106, frozen in liquid nitrogen and stored for 10 days. The values for fresh and thawed samples were: motility: 43.3 and 16.4% (p<0.05), viability: 48.3 and 40.5%, normal morphology: 67.1 and 56.5%, and integrity of the plasma membrane (HOS): 48.3 and 45.5%.